THE USE OF INNOVATIVE IDEAS IN TEACHING PHYSICAL EDUCATION (Conferencea, 2022)
The importance of the science of physical education in the maturation of physically strong, healthy, strong-willed and spiritually refreshed children is extremely great. Theoretical knowledge in the course process leads boys and girls to spiritual maturity, spiritually strengthens them, further increases their intelligence and ingenuity. In the process of education, students acquire knowledge about personal and nutritional hygiene, planning a daily routine, the importance of morning badantarbia exercises.